62+25=25+___ what's the answer? I'm only 2 grade

Answers

Answer 1
Answer:

Answer: 62

Step-by-step explanation: 25 appears on both sides, so you can cancel them out. This leaves a 62 on the left side, so there also must be a 62 on the right side.


Related Questions

(x^2 - x^(1/2))/(1-x^(1/2))
If the nth term of a sequence is 12n+2 what is the 7th term
If y − 3 = 3x, which of the following sets represents possible inputs and outputs of the function, represented as ordered pairs?A. {(0, 3), (1, 6), (2, 9)} B. {(3, 0), (6, 1), (9, 2)} C. {(1, 3), (2, 6), (3, 9)} D. {(3, 1), (6, 2), (9, 3)}
Can anyone help quickly.. explanation is not necessary but would be appreciated, I struggle with this topic and would like to understand it a little bit.
jalil and Victoria are each asked to solve the equation ax – c = bx + d for x. Jalil says it is not possible to isolate x because each x has a different unknown coefficient. Victoria believes there is a solution, and shows Jalil her work:

Two competing gyms each offer childcare while parents work out. Gym A charges $9.00 per hour of childcare. Gym B charges $0.75 per 5 minutes of childcare. Which comparison of the childcare costs is accurate?

Answers

Answer:

Gym B and Gym A charge the same hourly rate for the children.

Step-by-step explanation:

They are the same amount. if you divide 60 by 5 it is 12 and when you multiply .75 by 12 it equals 9. so Both are $9.00 an hour. 

Determine the type and number of solutions of 7x^2+3x+8=0

Answers

7x^2+3x+8=0 \n \na =7, \ b=3 ,\ c=8 \n \n\Delta =b^2 - 4ac = 3^2 -4\cdot 7\cdot 8=9-224=-215\n \n Answer : \ \Delta \ is \ negative,\ this \ gives \ two \ imaginary \ solutions


7x^2+3x+8=0\n\n \Delta=3^2-4\cdot7\cdot8=9-224=-115\ \ \Rightarrow\ \ \ no\ real\ solution\n\n\ two\ complex\ solutions\n\n\Delta=-115=115\cdot i^2\ \ \ \Rightarrow\ \ \ √(\Delta) = √(115)\ i\n\nx_1= (-b- √(\Delta) )/(2a) = (-3- √(115)\ i)/(2\cdot 7) = (-3- √(115i))/(14)\n\nx_2= (-b+ √(\Delta) )/(2a) = (-3+ √(115)\ i)/(2\cdot 7) = (-3+ √(115)\ i)/(14)

Mr. Morgan has five daughters. They were all born the number of years apart as the youngest daughter is old. The oldest daughter is 12 years older than the youngest. What are the ages of Mr. Morgan's daughters?

Answers

Representing the scenario as an equation,the ages of Mr. Morgan's daughters are 3,6,9,12 and 15.

Given the parameters:

  • Number of daughters = 5

owing to constant difference between their ages :

  • Let 'oldest' = 5a , 'youngest' = a

Since we are told that the difference between the ages of the youngest and oldest is 12 :

  • 5a - a = 12

5a - a = 12

4a = 12

a = 12/4

a = 3

Youngest is 3 ;

oldest = 5(3) = 15

The ages of the other 3 will be ;

  • 3 * 2 = 6
  • 3 * 3 = 9
  • 3 * 4 = 12

Hence, their ages are 3,6,9,12 and 15.

Learn more on word problems: brainly.com/question/25693822

#SPJ2

x, 2x, 3x, 4x, 5x

5x - x = 12

x = 3

The youngest is 3 and the oldest is 15.

The ages are: 3, 6, 9, 12, 15

Which unit would you use to measure the length of a football field?mm
cm
m
km

Answers

✔mm (milometer) ✅ yea

In the equation x^2 + 10x + 24 = (x + a)(x + b), b is an integer. Find algebraically all possiblevalues of b.

Answers

To factor (x² +10x+24); you first have to ask yourself, what 2 numbers will multiply and give me positive 24, but add and give me positive 10? After listing your factors, (1,24)(2,12)(3,8)and (4,6); you decide that (4*6)=24 & adds to get you 10. Meaning that (x²+10x+24) factors are (x+4)(x+6)
Now algebraically, there wouldn't be any other possible value of b, 6, because if you put (-6) & (4), those numbers will multiply and give you (-24) and add & give you (-2); & that is not what you're looking for. 

I hope I explained this enough for you to understand. (:

Remove all grouping symbols and combine like terms,
a - { a - [ a- (2a - b) + 3a ]}

Answers

a -\{ a - [ a- (2a - b) + 3a ]\}=\n a -\{ a - [ a- 2a + b + 3a ]\}=\n a -\{ a - [ 2a+b ]\}=\n a -\{ a - 2a - b \}=\n a -\{ - a- b \}=\n a+a+b=\n 2a+b
a - { a - [ a- (2a - b) + 3a ]}
= a - {a - (a - 2a + b + 3a)}
= a - {a - (2a + b)}
= a - (a - 2a -b )
= a - (-a - b)
= a + a + b
= 2a + b